THE RADIOECOLOGICAL CHARACTERISTIC OF THE RADIOACTIVE WASTE DISPOSAL SITES OF URANIUM PRODUCTION AND RECOMMENDATIONS FOR THEIR IMPROVEMENT - O. L. Ten (Радиационная гигиена)
This article deals with the issues of management of the uranium industry wastes at the territory of the Republic of Uzbekistan. The characteristics of the main uranium deposits and mining methods are given. The environmental problems associated with presence of large areas occupied by the uranium industry wastes and with the influence of natural processes on the integrity of such storage places are discussed. The author gives a generalized description of the measures on improving radiation situation in the ecosystems at contaminated territories and facilities of the country. The efforts of the State in relation to the remediation of contaminated land on dangerous facilities are described. The main directions of responsibility and control of radiation safety at the territories containing the uranium industry wastes are indicated. Based on the analysis, the author highlights promising areas of the state policy to improve the system of protective actions to reduce existing or unregulated radiation risks. The main tasks in the field of protection of public health and the environment are defined in the paper.